Viranomaisten toimivaltuudet kohteiden suojaamisessa hybridiuhkia vastaan - Järvenpää, Marika (Tiede ja ase, 2017)
New types of threats require security authorities to be prepared to adopt flexible readiness adjustment measures and to update these measures when necessary. If the crisis time legislation is yet not applicable, the Defense Forces work in cooperation with the Police by giving a requested assistance e.g. in target protection. According to the relevant provisions, reservists cannot be used to provide armed assistance for law enforcement, excluding cases of territorial defense. e modes of action available for utilizing reservists mainly rely on the right of self-defense and the general right of apprehension. Being able to fully utilize competent troops of reservists, as trained in troop production, requires a legislative change. is article is based on writers Master’s thesis in National Defense University 2016. It evaluates current legislation in terms of protection of critical facilities which may be the targets of cyber war.